The impact of ejaculatory dysfunction upon the sufferer and his partner - Abdo, Carmita Helena Najjar (Transl Androl Urol, 2016)
Ejaculatory function cannot be evaluated outside the dyadic process and without taking into account the men’s and women’s cognition of the condition and how their subjective perception impacts on the evaluation of the relationship and sexual quality. Although the distress of the sufferer and his partner has been a motivating factor in leading men with ejaculatory dysfunction to seek medical help, few objective or prospective evaluations of the effects on the couple have been reported. Specialized literature has been dealing with ejaculatory disorders in a heterogeneous manner. Comparatively, there are far more studies on premature ejaculation (PE) than on delayed ejaculation (DE) and even fewer studies on other male orgasm disorders. Therefore, the review focuses on the literature of the two most studied ejaculatory disorders. The matter presented in this article can also be considered for other ejaculatory disorders, since all of them relate to a failure of control, changing the intravaginal ejaculatory latency time (IELT), with consequences for men and their partners. There are multiple psychological explanations as to why a man develops PE or DE. Unfortunately, none of the theories evolve from evidence-based studies. The common final pathway of these factors is the irrational fear of ejaculating intravaginally. These sexual disorders may also cause personal distress for the sexual partner and decreased sexual satisfaction for the couple. An association between pre-existing anxiety disorders and sexual performance anxiety has been found in men and couples with ejaculatory dysfunction. This could reflect a process in which pre-existing anxiety triggers sexual dysfunction, causing performance anxiety and leading to a vicious cycle: anxiety, sexual dysfunction, more anxiety. Men with DE are similar to men with other sexual dysfunctions. They show the same elevated level of sexual dissatisfaction and they also show lower levels of coital frequency. To a lower extent, they use more masturbatory activity relative to controls. The burden of PE for the patient is revealed in three different levels: the emotional burden, the health burden, and the burden on the relationship. In terms of the emotional burden, there is often a sense of embarrassment and shame at not being able to satisfy their partner, and patients often have low self-esteem, feelings of inferiority, anxiety, anger, and disappointment. Men feel frustrated about their PE and how it affects their intimacy with their partners and the sexual relationship. In conclusion, ejaculatory dysfunction has a negative impact on both the man and his female partner and, consequently, it has implications for the couple as a whole. Additionally, ejaculatory dysfunction extending beyond a year elevates the risk of depression in these patients. Although partner perceptions of PE generally indicated less dysfunction than those of subjects, partner outcomes measures play a part in the assessment of PE. Ejaculatory dysfunction involves the integration of physiological, psychobehavioral, cultural, and relationship dimensions. All these elements need to be considered in the treatment.